2022
DOI: 10.1177/10781552221079356
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab for advanced non-small cell lung cancer (NSCLC): Impact of autoimmune comorbidity and outcomes following treatment completion

Abstract: Introduction Pembrolizumab, an immune-checkpoint inhibitor, is approved for first-line treatment of metastatic NSCLC in patients with tumours expressing programmed death-ligand 1 (PD-L1) with tumour proportion score (TPS) of ≥50%. We aimed to clarify some uncertainties regarding use of immunotherapy in patients with previous autoimmune (AI) disorders and assess real-world outcomes following treatment completion. Methods We performed a retrospective case record review of 82 patients with tumours expressing PD-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Among these, three studies were from Japan, 20 , 21 , 24 one from Korea, 28 two from Italy, 22 , 32 one from France, 25 two from Germany, 26 , 33 one from the UK, 29 one from Switzerland, 23 one from Holland, 27 and two from the US. 34 , 35 Nine studies reported on non-small cell lung cancer (NSCLC), 20–22 24 , 25-28 29-33 35 seven on melanoma, 22–25 27–32 34 , 35 and three on metastatic renal cell cancer and urothelial carcinomas. 22 , 23 , 35 Among AIDs, ILD and endocrine AID were most frequently mentioned.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these, three studies were from Japan, 20 , 21 , 24 one from Korea, 28 two from Italy, 22 , 32 one from France, 25 two from Germany, 26 , 33 one from the UK, 29 one from Switzerland, 23 one from Holland, 27 and two from the US. 34 , 35 Nine studies reported on non-small cell lung cancer (NSCLC), 20–22 24 , 25-28 29-33 35 seven on melanoma, 22–25 27–32 34 , 35 and three on metastatic renal cell cancer and urothelial carcinomas. 22 , 23 , 35 Among AIDs, ILD and endocrine AID were most frequently mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…R software (version 4.1.3) was used for data analyses. RR was used to re ect the incidence of irAEs of any grade and grade ≥ 3 [15][16][17][18][19][20][21] . If the studies recorded HR for PFS or OS, we adopted the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations